Challenging the extended phenotype: HRD-negative salivary gland carcinoma in a BRCA1 founder-variant carrier, case report and literature review - Torres, William; Vargas, Elizabeth; Ballen, Diego-Felipe; Tapiero-Rodriguez, Sandra M; Cadena, Enrique; Parra-Medina, Rafael; Riaño-Moreno, Julian C (Frontiers in Oncology, 2026)
BackgroundPathogenic BRCA1 variants are established in hereditary breast and ovarian cancer (HBOC) and associated with pancreatic, prostate, and gastric cancers. Salivary gland tumors (SGTs) have been reported in BRCA1/2 carriers and suggested as part of an extended HBOC phenotype based on epidemiological associations. However, functional evidence is lacking, and homologous recombination deficiency (HRD)—the hallmark of BRCA-driven cancers—has not been systematically assessed in BRCA1-associated SGTs.Case presentationWe report a Colombian family segregating the BRCA1 c.3331_3334delCAAG (p.Gln1111Asnfs*5) founder variant with phenotypic variability across four generations: gastric (31%), breast (37.5%), colorectal (19%), and thyroid cancers (12.5%). The proband, a 61-year-old woman, developed high-grade mucoepidermoid carcinoma of the parotid gland. Germline testing confirmed the familial BRCA1 variant. Tumor profiling revealed the same BRCA1 variant (VAF 56%) plus a pathogenic TP53 mutation (c.730G>T, p.Gly244Cys; VAF 32%), without BRCA1 loss of heterozygosity. HRD testing using shallow whole genome sequencing showed preserved homologous recombination function (Genomic Instability Score: 0.01, LGA: 11.40, LPC: 0), all below HRD-positive thresholds.ConclusionThis represents the first SGT in a BRCA1 carrier evaluated with HRD testing. The absence of HRD argues against BRCA1-driven tumorigenesis despite clear familial segregation. These findings challenge the presumed causal relationship between BRCA1 variants and SGT development. Clinical implications are direct: SGTs in BRCA1 carriers should not be assumed eligible for PARP inhibitor therapy without HRD confirmation, and enhanced surveillance appears unwarranted. This case underscores that co-occurrence does not establish causation and highlights the critical importance of functional validation before expanding hereditary cancer spectra.